Thermal properties and chemical conversion of a trifunctional epoxy resin cured with aromatic amine / Zakaria Man, Nor Yuliana Yuhana and Ruzaimah Nik Mohd Kamil - Man, Zakaria; Yuhana, Nor Yuliana; Nik Mohd Kamil, Ruzaimah (2006)
The thermal properties such as evolution of glass transition temperature, Tg with curing time and reaction conversion of a triglycidyl p-amino phenol (TGpAP) cured with 4, 4 '-diaminodiphenyl sulfone (DDS) are difficult to measure. In this study, dynamic mechanical analysis (DMA), differential scanning calorimeter (DSC) and temperature modulated differential scanning calorimeter (TMDSC) were used to characterize the TGpAP/DDS samples cured at 180°C The results show that DMA is not sensitive enough to detect the evolution of Tg with curing time and the peak exortherm of DSC curves overlapped with Tg. Two different maximum Tg values were obtained from using two different equipment. DMA results show that the epoxy reached the maximum Tg after 90 minutes cured at 180°C while the maximum Tg obtained from TMDSC was 236°C after 150 minutes. The result from TMDSC seems more accurate because the evolution of Tg and chemical conversion can be followed starting from the beginning of the reaction until vitrification. At the maximum Tg the chemical conversion attained was 93% The Tg of 236°C, which is higher than file curing temperature, Tc(180°C) or Tg > Tc is due to the reactive nature of the TGpAP/DDS system.